ANALYSIS OF KARL MARX'S THOUGHT IN "VALUE, PRICE AND PROFIT" ON THOMAS KUHN’S SCIENTIFIC PARADIGM AND UMAR BIN KHATTAB’S FIQH OF ECONOMIC - Zulfikar Adib Agamawan (Journal of Management and Islamic Finance, 2021)
This study examined the relationship between Karl Marx’s thought and the concept of Thomas Kuhn's paradigm. The thought of Karl Marx employed in this article is a copy of Karl Marx's speech entitled "value, price and profit". The Karl Marx’s thought was analyzed using the four phases of science development from Thomas Kuhn. Furthermore, the thought of Karl Marx was also reviewed in terms of Islamic Economics, particularly Umar bin Khattab’s Fiqh of Economic. The methodology used in this research is a literature review with various references related to the issues raised. The results of the analysis present that Karl Marx's thought contained in the speech "value, price and profit" fulfill the four phases of science development from Thomas Kuhn. The thought of Karl Marx also possesses some similarities with the concept of distribution of Umar bin Khattab.